Job Relocation and Its Predictors in Indonesian Public Sector - Roby Syaiful Ubed (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2018)
ABSTRACT This study is aimed to be a preliminary research related to job relocations in Indonesian public sector, mainly in Ministry of Finance Indonesia. Interviews with employees experiencing job transfers were conducted to further analyze the predictors of job transfers. Results of this research revealed that there are some factors affecting positively to willingness to transfer such as career opportunity, clear transfer path, obligation of officials, culture, and new skills and knowledge. In addition, there are also some factors affecting negatively to willingness to transfer such as initial information, social attachment, pension, unclear transfer path, fairness perception, financial problems, children, spouse’s career, geographic location, and adjustmen in new workplaces. Keywords: job transfer, predictors, relocations